"Spanish Palliative Care Nurses' Degree of Acceptance of a Proposal for Nursing Competencies in Palliative Care". Issue 3 (July 2022) - Lourdes, Guanter-Peris; Ainhoa, Molins-Mesalles; Benito-Aracil, Llúcia; Solà-Pola, Montserrat; Pla i Consuegra, Margarida
Background: In Spain, palliative care (PC) nursing is not a recognized specialization and PC nurses do not receive systematic specialized academic training in PC. To ensure the quality of PC in Spain, the Spanish Association of Palliative Care Nursing has been working since 2011 to design a model of competencies for PC nurses.Objective: Verify whether a sample of Spanish PC nurses accepts the proposed model of PC nursing competencies describing their work.Methods: Descriptive cross-sectional observational study based on an ad-hoc questionnaire about 98 proposed competencies, which participants rated for whether they belong to the purview of PC nurses and for their degree of concordance with their own practice and their degree of importance in PC nursing. Competencies receiving approval by more than 75% of participants for the three dimensions were considered to have been accepted by consensus. Mixed logistical models were developed to study the association between demographic variables and the responses.Results: Sixty-two out of 98 proposed competencies were accepted by more than 75% of participants. We therefore considered these competencies to have been accepted by consensus. Thirty-six proposed competencies failed to meet the threshold of 75% acceptance. For competencies that were accepted overall, participants with more than 10 years of experience in PC and participants with specialized training in PC were more likely to report that these competencies were part of the purview of PC nursing. Participants age >50 were less likely to report that competencies related to research concorded with their practice. Participants accepted the importance of all 98 proposed competencies.Conclusion: The variables of experience, training and age had a statistically significant relationship with the acceptance or rejection of the proposed competencies on the basis of purview and concordance. Further research is necessary to understand more fully these relationships to eventually arrive at a consensus model for the competencies of PC nurses.